Challenges of the Modern World in the Educational Field: Mixed Methods on Depression, Anxiety & Stress, GPA, OCB & Dropouts Rate in UK, Ireland & Spain - Samuel PD Anantadjaya; Irma M. Nawangwulan; Timotius A. Rachmat; Pikat AR Muqaddasah (Transpublika Publisher, 2026)
This study examines how depression, anxiety, and stress affect academic performance, Organizational Citizenship Behavior (OCB), and dropout risk among adolescents in technical and vocational education institutions across the United Kingdom, Ireland, and Spain. Given rising mental health concerns, educators and researchers prioritize understanding how these issues shape educational outcomes. A mixed-methods approach combined quantitative analysis and narrative inquiry. Quantitatively, Structural Equation Modeling (SEM) using IBM SPSS AMOS tested links between depression, anxiety, stress, Grade Point Average (GPA), OCB, and dropout risk using data from 1,456 students aged 15-18. Qualitatively, semi-structured interviews explored lived experiences and views on mental health and academic engagement. Results showed depression, anxiety, and stress significantly lowered GPA and OCB while increasing dropout risk. Stress was the strongest predictor across outcomes. Qualitative themes included emotional overload, academic fatigue, social withdrawal, and institutional troubles. Students reported stress as the most immediate influence on learning, social participation, and educational persistence. Cross-national comparisons showed consistent relationships, though effect sizes varied by educational and socio-cultural context. The study concludes mental health is a major driver of educational success and retention in vocational education, supporting broad mental health interventions, early support mechanisms, and policy actions to improve student well-being, academic outcomes, and long-term educational trajectories.